TAKEOVER DEFENSES, OWNERSHIP STRUCTURE AND STOCK RETURNS IN THE NETHERLANDS: AN EMPIRICAL ANALYSIS - Kabir, Rezaul; Cantrijn, Dolph; Jeunink, Andreas (Strategic Management Journal, 1997)
This study empirically examines the relationships between a firm’s takeover defenses and its ownership structure and stock returns. Analyzing data of Dutch listed companies, we find that multiple antitakeover defenses are increasingly adopted when firms are characterized by relatively lower ownership concentration. The evidence supports the hypothesis that more concentrated ownership of shares provides more effective monitoring of managers. As defense by issuing preferred share has recently been the most widely adopted mechanism in the Netherlands, its impact on shareholders’ wealth is also analyzed. We observe the presence of two opposing effects of this antitakeover measure. © 1997 by John Wiley & Sons, Ltd.